2006
DOI: 10.1111/j.1365-2303.2006.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cervicovaginal smear screening: method of quality control and assessing individual cytotechnologist performance

Abstract: RS could be introduced as an efficient method of quality control to improve the sensitivity of cytological screening as well as for quality control of cytotechnologist performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
13

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 31 publications
0
18
0
13
Order By: Relevance
“…That the examiner was aware there were not only normal smears but also abnormal ones in that batch of smears may explain these findings, and this is precisely the benefit of rapid prescreening. 17,28,[39][40][41] It is already known that the principal difference between rapid prescreening and 100% rapid review is that rapidly screening only those smears considered normal or unsatisfactory at routine screening means evaluating a group of smears in which the incidence of abnormality is low. This is a tedious task that may reduce concentration and result in screening errors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That the examiner was aware there were not only normal smears but also abnormal ones in that batch of smears may explain these findings, and this is precisely the benefit of rapid prescreening. 17,28,[39][40][41] It is already known that the principal difference between rapid prescreening and 100% rapid review is that rapidly screening only those smears considered normal or unsatisfactory at routine screening means evaluating a group of smears in which the incidence of abnormality is low. This is a tedious task that may reduce concentration and result in screening errors.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,24,29,33 Rates of false-negative results of 1.80% and 1.14% identified by rapid prescreening and 100% rapid review, respectively, were consistent with those reported from other studies, in which the rate of false-negative results ranged from 0.0% to 9.8% with rapid prescreening and from 1.07% to 33.1% with 100% rapid review. 9,15,20,28,[34][35][36][37][38] What, then, would explain that one method is more sensitive than the other despite both methods using the same rapid-screening technique? Why was sensitivity higher in some studies evaluating the 100% rapid review method compared with others that evaluated the same technique?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most used techniques are the review of 10% (R-10%) of negative smears at routine screening (RS) and cases with clinical risk criteria (CRC). These methods have been recommended in both the USA and Brazil [5,6] but they have proved ineffective for evaluating the performance of RS [3,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…13 A study investigating the effectiveness of rapid review as a quality control measure for negative slides also implicated abnormal HCCG in cases of missed dyskaryosis. 14 The current NHSCSP audit of invasive cervical cancers has specified microbiopsies as a potential cause of missed dyskaryosis and has listed several benign forms of HCCG as causes of false-positive reports. 15 Such groups are also listed as problems in interpretation of dyskaryosis.…”
Section: Significancementioning
confidence: 99%